Uptake of hexavalent chromium by Lactuca sativa and Triticum aestivum plants and mediated effects on their performance, linked with associated public health risks. (March 2021) - Christou, Anastasis; Georgiadou, Egli C.; Zissimos, Andreas M.; Christoforou, Irene C.; Christofi, Christos; Neocleous, Damianos; Dalias, Panagiotis; Fotopoulos, Vasileios
Abstract: Plants exposed to toxic Cr(VI) concentrations show reduced biomass production and yield. The present study examined (1) the impacts of increasing Cr(VI) exposure (0.05, 0.5, 1, 5 and 10 mg L −1 K2 Cr2 O7 in irrigation water) on the growth and development, yield, and stress physiology of two important crop species, such as wheat ( Triticum aestivum L.) and lettuce ( Lactuca sativa L.), and (2) the associated human health risks due to the consumption of these commodities. Plants in all Cr(VI) treatments preserved similar growth rates and phenotypes with control, untreated plants, with no remarkable modulations in biomass yield (fresh/dry weight, plant height, straw/grain weight). Grains harvested from plants exposed to all Cr(VI) treatments had increased size and 1000 grain weight, partially suggesting hormetic effect. Elevated K2 Cr2 O7 concentrations (5 and 10 mg L −1 ) resulted in increased photosynthetic pigments' levels in lettuce leaves. Lipid peroxidation and H2 O2 content also revealed the absence of oxidative stress in lettuce plants. Non-carcinogenic (target hazard quotient) and carcinogenic risks from the consumption of these commodities grown under the conditions described in this study were found de minimis . However, more studies are needed in order to obtain more solid information on the safety of Cr(VI)-contaminated water irrigation. Graphical abstract: Image 1 Highlights: Wheat and lettuce plants were exposed to Cr(VI) in an agricultural setting. Cr(VI) exposure din not affect the biomass yield of both plant species. Exposure to K2 Cr2 O7 (up to 10 mg L −1 ) resulted in wheat grains with enlarged size. Plants did not suffer oxidative damage due to Cr(VI) exposure (up to 10 mg L −1 ). Risk assessment revealed the absence of any public health risks.